2006
DOI: 10.1152/ajpcell.00509.2005
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial response to stress from exogenous Zn2+ resembles that of NO-mediated nitrosative stress, and is protected by MT-1 overexpression

Abstract: While nitric oxide (NO)-mediated biological interactions have been intensively studied, the underlying mechanisms of nitrosative stress with resulting pathology remain unclear. Previous studies have demonstrated that NO exposure increases free zinc ions (Zn(2+)) within cells. However, the resulting effects on endothelial cell survival have not been adequately resolved. Thus the purpose of this study was to investigate the role of altered zinc homeostasis on endothelial cell survival. Initially, we confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 57 publications
(71 reference statements)
3
68
0
1
Order By: Relevance
“…We demonstrated that apical exposure to ZnO NPs for 24 hours reduced mitochondrial activity ( Figure 12). Mitochondrial dysfunction is partly associated with depletion of sulfhydryl groups in metallothionein-1 proteins caused by excess Zn 21 arising from dissolved ZnO NPs (43,44). Our data suggest that excess free Zn 21 (from dissolved ZnO NPs) disrupts zincprotein interactions in mitochondria, leading to disruption of mitochondrial redox state and an increase in intracellular ROS levels, resulting in cell plasma membrane damage and cell injury.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We demonstrated that apical exposure to ZnO NPs for 24 hours reduced mitochondrial activity ( Figure 12). Mitochondrial dysfunction is partly associated with depletion of sulfhydryl groups in metallothionein-1 proteins caused by excess Zn 21 arising from dissolved ZnO NPs (43,44). Our data suggest that excess free Zn 21 (from dissolved ZnO NPs) disrupts zincprotein interactions in mitochondria, leading to disruption of mitochondrial redox state and an increase in intracellular ROS levels, resulting in cell plasma membrane damage and cell injury.…”
Section: Discussionmentioning
confidence: 79%
“…Excess Zn 21 in mammalian cells is toxic, although a trace amount of Zn 21 serves as an effective antioxidant and a critical structural and functional component of zinc-binding proteins (40,41). Impaired mitochondrial function due to increased intracellular Zn 21 causes elevated intracellular ROS, leading to apoptotic or necrotic cell death (42)(43)(44). Recently, Nel and colleagues (30) reported that cytotoxicity of ZnO NPs may be directly related to dissolution of ZnO NPs suspended in bathing medium of RAW 264.7 and BEAS-2B cells, and Lin and colleagues (24) showed that viability of A549 cells is reduced in a dose-and time-dependent manner after apical exposure to ZnO NPs.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of Zn 2ϩ as a potent intracellular TRPA1 activator makes it likely that cellular stressors that increase [Zn 2ϩ ] i (44,45) will activate TRPA1 and affect the excitability of neurons. Our results also raise the possibility that TRPA1 can be activated indirectly in response to Zn 2ϩ entry through other neuronal ion channels, such as L-type Ca 2ϩ and AMPA/kainate channels (23,46), which are expressed by DRG neurons (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…9). These considerations suggest that when the proton pump is disabled accumulation of Zn 2ϩ during different forms of cellular stress (38,43) could lead to undue or untimely accumulation of Zn 2ϩ in the cytoplasm, and thence to a variety of disturbances in cell viability and function (36,37).…”
Section: Discussionmentioning
confidence: 99%